Conversations with leading economists : interpreting modern macroeconomics - Snowdon, Brian; Vane, Howard R. (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar, 1999)
This book provide their readers with a thoughtful introductory essay outlining the development of microeconomics since the 1930s, and the themes that they deal with there occur and re-occur throughout their interviews, and bringing considerable unity to the book as a whole.
Interviews with 14 economists.
gau 24/01/14
Loans
Keywords: Macroeconomics; Economists -- United States -- Interviews; Economists -- Great Britain -- Interviews